Determination of Indonesian Islands Sea Lane as a Tools of Providing Legal Certainty for Foreign Flag Vessels Through Indonesian Waters: Penetapan Alur Laut Kepulauan Indonesia sebagai Sarana Pemberian Kepastian Hukum bagi Kapal Berbendera Asing yang Melalui Perairan Indonesia - Pramono, Budi; Pramono, Agung; Umar, R. Isyack (Faculty of Law Hang Tuah University, 2025)
This research discusses the current determination of Archipelagic Sea Lanes determined by the Indonesian government which is able to provide legal certainty for foreign-flagged ships crossing Indonesian waters. The problem that arises with the determination is whether they do not create vulnerabilities that have the potential to harm the national interests of the Indonesian people. This research is normative legal research with a conceptual and statutory approach. The research results show that the Indonesian government has established archipelagic sea lanes so that it can provide legal certainty for foreign ships crossing Indonesian waters. This determination is a mandate from the ratification of the 1982 international maritime law convention. However, this determination still creates vulnerabilities that have the potential to harm the national interests of the Indonesian people. The cause of this vulnerability is because the norms contained in the regulations regarding archipelagic sea lanes does not contain sanctions norms so that legal violations often occur in the archipelagic sea lanes area. The need for more significant sanctions is due to the fact that archipelagic sea lanes have specificities compared to other maritime zones.